An X‐ray beam profile monitoring system at a beamline front‐end combining a single‐crystal diamond film and energy discrimination using droplet analysis. (20th April 2022) - Kudo, Togo; Sano, Mutsumi; Matsumoto, Takahiro; Itoga, Toshiro; Goto, Shunji; Takahashi, Sunao
Abstract : A beam monitoring system with pin‐hole optics has been developed at an undulator beamline front‐end in SPring‐8. Energy‐resolved beam images were successfully observed and were found to be in good agreement with the theoretical calculation. Abstract : This work has successfully demonstrated a system for monitoring pink‐beam X‐rays exiting from a beamline front‐end, which has a specific spatial distribution based on each energy component. In this study, the X‐rays scattered from a single‐crystal chemical‐vapor‐deposited diamond film were converted into a cross‐sectional image using pinhole optics, followed by digitization with a direct detection complementary metal‐oxide‐semiconductor 2D detector. By using single crystals instead of poly‐crystals, good quality images were obtained with no diffraction bright spots. As a result of applying photon energy discrimination using the droplet analysis to the image information, the spatial distribution of each energy component of the undulator radiation was successfully visualized. The result was found to be in good agreement with the theoretically calculated result obtained using the synchrotron radiation calculation code SPECTRA . The new synchrotron radiation beam monitor proposed in this paper can serve as a powerful beam diagnostic tool for diffraction‐limited rings that require strict light source stability.